KLARIFIKASI ASIMILASI DAN INTEGRASI NARAPIDANA DITENGAH PANDEMI COVID-19 - Pristya Noptiaranika (Universitas Muhammadiyah Tapanuli Selatan, 2021)
This research focuses on the assimilation and integration policy which is given to convicts in an effort to inhibit or break the rate of the spread of Corona viruses which is the authority of the Indonesian Government through the Ministry of Law and Human rights RI. However, the granting of this policy makes the occurrence of feud with the wider community, the feud is the disapproval of society with the provision of this policy. The author then examines this problem using qualitative approach methods. With the approach of law and case studies. Data obtained through news published on social Media. Through this study, it is expected to answer the community questions about why the assimilation and integration of prisoners are given. The purpose of this research is to give an overview and clarification explanation to the community to the policy of the Government of Indonesia through the Ministry of Justice and Human Rights of the Republic of Indonesia about the provision of assimilation and integration given to prisoners amid pandemic Covid-19. So that people can understand and know for the reason this habit is given